2019
DOI: 10.3390/nu11061248
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Stevia (Rebaudioside A) Consumption Perturbs Gut Microbiota and the Mesolimbic Dopamine Reward System

Abstract: Stevia is a natural low-calorie sweetener that is growing in popularity in food and beverage products. Despite its widespread use, little is understood of its impact on the gut microbiota, an important environmental factor that can mediate metabolism and subsequent obesity and disease risk. Furthermore, given previous reports of dysbiosis with some artificial low-calorie sweeteners, we wanted to understand whether prebiotic consumption could rescue potential stevia-mediated changes in gut microbiota. Three-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 61 publications
2
47
0
2
Order By: Relevance
“…However, only stevia rebaudioside A increased SCFAs acetate and valerate, which are positively correlated with fat mass and total weight. Hence, stevia rebaudioside A seems to decrease the "healthy" status of the gut microbiota [55].…”
Section: Steviol Glycosidesmentioning
confidence: 99%
“…However, only stevia rebaudioside A increased SCFAs acetate and valerate, which are positively correlated with fat mass and total weight. Hence, stevia rebaudioside A seems to decrease the "healthy" status of the gut microbiota [55].…”
Section: Steviol Glycosidesmentioning
confidence: 99%
“…Fecal matter was collected at three, seven, and 11 weeks of age, snap-frozen, and stored at −80 • C. Microbial profiling was performed based on our previous work [22][23][24]. Briefly, bacterial DNA was extracted from~60 mg of stool using the FastDNA spin kit for feces (MP Biomedicals, Lachine, QC, Canada).…”
Section: Bacterial Dna Extraction and Microbiota Analysismentioning
confidence: 99%
“…Half of the extracted sample was brought to a concentration of 4 ng/µL prior to storage at −20 • C for qPCR analysis, and the other half was used for 16S ribosomal RNA (rRNA) sequencing at the Center for Health Genomics and Informatics at the University of Calgary. Quantitative PCR (qPCR) was carried out as previously described [22][23][24] with primers that covered the major gut bacterial groups in rodents (Table S2, Supplementary Materials).…”
Section: Bacterial Dna Extraction and Microbiota Analysismentioning
confidence: 99%
“…Studies have reported that mice consuming 0.1 mg mL −1 of pure saccharin (equivalent to 5 mg/kg BW) [137] and 2–3 mg/kg BW stevia [138] induce dysbiosis in the gut microbiota, with mixed evidence for 1.1–15 mg/kg BW per day of sucralose [136,139]. Furthermore, the dysbiosis in the gut was associated with glucose intolerance in mice consuming 0.1 mg mL −1 of pure saccharin on a HFD [137], while the change in the gut microbiotadid not affect BW, food intake or insulin sensitivity in rats consuming 2–3 mg/kg BW of stevia [138]. However, food and water intake was only measured in a subset of mice consuming 0.1 mg mL −1 of pure saccharin, and may not be representative of the entire population [131,137].…”
Section: Microbiotamentioning
confidence: 99%